Calculation and optimization of inter-regional available transfer capability considering wind power uncertainty and system improvement measures - Liu, Wenli; Zhang, Tao; Yang, Xiaolei; Wang, Jin (Frontiers in Energy Research, 2023)
This paper examines the impact of wind power stochastic characteristics on the available transmission capacity(ATC) and then explores ways to alleviate transmission congestion from the grid and load side respectively. The impact of stochastic variables is considered by generating typical scenarios. In terms of improving ATC, this is achieved by optimally allocating thyristor controlled series compensation (TCSC) on the grid side and adopting demand response(DR) on the load side. Methods of applying latin hypercubic sampling(LHS) and backward reduction techniques to generate typical wind power scenarios, the equivalence of TCSC in steady-state calculations and the calculation of DR are derived. A model for source-network-load cooperative optimisation of ATC is established. The model solution part adopts the improved particle swarm optimization(PSO) algorithm, which improves the computational performance by adjusting the initial particle formation method and the iteration process of the standard algorithm. Finally, based on the IEEE-30 node system, an experimental scheme is designed for experimental verification. The results show that: DR is effective in improving the lower bound of ATC fetch interval; the reasonable configuration of TCSC is especially beneficial in improving the upper bound of ATC fetch interval; and the joint application of the two measures contributes to the comprehensive improvement of ATC. The work done in this paper contributes to the improvement of ATC, which can achieve the purpose of promoting new energy consumption by improving the utilisation efficiency of the transmission network without changing the network structure.